PERGESERAN KEDUDUKAN KOMISI PEMBERANTASAN KORUPSI (KPK) DALAM STRUKTUR KETATANEGARAAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 36/PUU-XV/2017 (Lex Jurnalica, 2020)
In 2006, the Constitutional Court placed the Corruption Eradication Commission (KPK) as an institution that deals with judicial authority in the constitutional systems according to the Constitutional Court's decision No. 012-016-019 / PUU-IV / 2006. Whereas a decade later, the Commision as a special executive institution that carries out the functions of inquiry, investigation and strive for corruption cases, so it leads the object of the DPR's questionnaire rights through the Constitutional Court's decision No. 36 / PUU-XV / 2017. This paper will discuss some issues; How is the shift of the Corruption Eradication Commissionâ€™s position in the constitutional structure after the final decision of the court and How is the consideration of the Judges in making decision Number 36 / PUU-XV / 2017. This is a normative legal research. Â Keywords: House of Representatives, Corruption Eradication Commission, Constitutional Court.Â